Entrepreneurship Education and Career Choice of Secondary School Students in Lagos, Nigeria - Longe, Olubukola Oluwadaisi (NIU Journal of Social Sciences, 2026)
This study examined the adequacy of entrepreneurship education and its influence on job perception and career choice among Senior Secondary School (SSS2) students in Mainland Local Government Area, Lagos State, Nigeria. Using a self-structured questionnaire, data was collected from 200 SSS2 students and analyzed with Pearson correlation and independent samples t-test at the 0.05 significance level.  Findings revealed significant positive relationships between adequate entrepreneurship education and students’ career choice, job interest, and entrepreneurial outcomes. A significant gender difference was also found in job perception, with male and female students differing in their views.  The study concludes that adequate entrepreneurship education significantly shapes students’ job perception and career choice. It recommends the inclusion of entrepreneurship education in the secondary school curriculum nationwide and urges guidance counselors to motivate and support students’ participation in entrepreneurial activities. Keywords: Entrepreneurship education, career choice, secondary students, job perception.